Pathological study of Stachybotrys chartarum that isolated from baths floor in Babylon province on some respiratory and digestive organs in white mice(Balb/c) - Abbas K . Al-Mansoori (Al-Qadisiyah Journal of Pure Science, 2018)
Stachybotrys chartarum is filamentous  fungi  that cause respiratory system infection in human and animals . This study was aimed  to evaluate histological changes in some  respiratory and digestive organs such as pharynx, trachea  and lung induced by this fungus suspension    . Detection of Stachybotrys chartarum fungus confirmed  by cultured  random samples that collected in clean containers from baths floor on potato dextrose agar  in room temperature for 7-14 days. Then  the suspension of positive samples of this fungus diluted by normal saline and counted the spores by using hemocytometer before used experimentally in lab animals (Balb mice) to study histological changes in some respiratory and digestive organs . Twelve mice used in this study divided into  two groups . first group consist of six mice  injected orally with   0.5 ml from one positive sample of fungus suspension contain 2Ã—103 spore / mm3(for month : one dose daily) according to count of hemocytometer to evaluate some pathological changes  in pharynx ,trachea  and lung .Second group injected  orally with 0.5 ml from phosphate buffer saline only. The results revealed that no changes in the pharynx  of mice infected with0.5 ml contain 2Ã—103 spore / mm3 from Stachybotrys chartarum  fungus suspension. the lung of group mice treated with same  concentration  of fungus  has interstitial pneumonia  with thickening  of inter alveolar  space  due to infiltration  and chronic inflammatory cells especially mononuclear cell.While the trachea of group mice treated with same  concentration  of fungus suffering sub mucosal   chronic inflammatory cells  and  infiltration  with  increase   thickness   of mucosal basal  layer  .